PERFORMANCE REWARD STRATEGIES AND TEACHERS’ COMMITMENT IN PUBLIC SECONDARY SCHOOLS IN TESO-NORTH SUB-COUNTY, KENYA - Juma, Sheila; Kikechi, Ronald Werunga; Ngome, Charles Kibanani (IJRDO-Journal of Applied Science, 2023)
The purpose of the study was to determine the extent to which performance reward strategies influence teachers’ commitment in public secondary schools in Teso-North Sub-County, Kenya. Descriptive survey research design was adopted study. The target population of the study was 1215 persons that encompassed 3 Sub- County Education officers and 1212 teachers from public secondary schools in Teso North Sub-County. Krejcie and Morgan (1970) Table was used to determine the sample size. Hence a target of 1212 persons gave a sample size of 291 persons. The study then used stratified random sampling technique to identify the respondents. Structured questionnaires and interviewing guides were the main primary data gathering tools for the study. The instruments were approved by the experts in subject area. A pilot study was used to determine the instrument’s reliability, of which they yielded a correlation coefficient (r) of 0.79. This demonstrated the instrument’s dependability. While qualitative data was broken down into themes as well as sub-themes and presented using quotations, quantitative data was, examined utilizing descriptive as well as inferential statistics and presented in tables. The study found a statistically significant relationship amongst teachers’ commitment as well as performance appraisal procedures, assessor feedback, objectivity, and performance reward strategies in public secondary schools. The research will help academics, decision-makers, and community people. Therefore, it can be, said that the performance evaluation system implemented by the Teachers’ Service Commission increased teachers’ dedication in public secondary schools.